THE STUDY OF THE STRUCTURAL AND DERIVATIONAL FEATURES OF THE TERMS OF WOOD TECHNOLOGY IN THE COURSE «THE PROFESSIONAL TERMINOLOGY» - Оксана Гриджук (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The derivational organizing of the Ukrainian wood technology terms is explored in the article; the most productive ways of formation are revealed and the derivational models of the wood technology terms are analyzed. The expediency of learning the ways of formation of professional terms and formants used for terms derivation by students of the forestry engineering specialties is justified. The variants of exercises for the derivational analysis of terms, the explanation of the ways of their formation, and the recognition of derivative formants, and the tasks of finding out the semantics of wood technology terms by the derivational type are proposed. It is proved that such exercises are necessary for the formation of the specialized language and terminology knowledge of the wood technology industry future workers.